(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study analyzes the competitiveness of Micro-Small-Medium Enterprises (SMEs) of doll industrial sector in West Java Province which is influenced by human capital, social capital, work environment, and productivity. The aim of this research is to know and analyze the influence of human capital, social capital, work environment directly to productivity. This research was using a survey method with a quantitative approach. The unit of analysis of this study is the doll industrial sector in West Java Province, with entrepreneurs as a unit of observation, namely a population of 191 entrepreneurs and a sample of 128 entrepreneurs. Data were obtained from survey results through questionnaires distributed to the entrepreneurs. Data were processed using statistical analysis and SEM-PLS analysis. The results showed that in the human capital, work environment, and productivity were tend to be high and social capital were tend to be low. Based on hypothesis testing, it is found that the human capital, social capital, and work environment have a positive effect on productivity; and that human capital, social capital, work environment, and productivity have a positive and significant effect on competitiveness, directly and indirectly